For richer for poorer : a novel - Steel, Danielle (New York : Delacorte Press, 2025)
"A loving mother and successful fashion designer struggles to keep her family together and her business afloat."--
Keywords: Fashion shows -- New York (State) -- New York -- Fiction; Man-woman relationships -- Fiction; Pregnant women -- Fiction; Real estate developers -- Fiction; Weddings -- Planning -- Fiction; Women fashion designers -- Fiction; Fashion designers -- Fiction; Women-owned business enterprises -- Fiction; Hamptons (N.Y.) -- Fiction; Romance fiction